National Anti-austerity Protests in a European Crisis: Comparing the Europeanizing Impact of Protest in Greece and Germany During the Eurozone Crisis. Issue 3 (3rd July 2017) - Roose, Jochen; Kanellopoulos, Kostas; Sommer, Moritz
ABSTRACT: Protest and social movements are drivers for the Europeanization of national public spheres. This is suggested by the literature on the emergence of Europeanized public spheres and the Europeanization of social movements as well as the discussion about the politicization of the European polity. The article tests this assumption in a standardized content analysis for newspaper reporting on the Eurozone crisis in Greece and Germany. Focusing on the public attribution of responsibility, the analysis looks for horizontal Europeanization (senders/addressees from other EU countries), vertical Europeanization (senders/addressees from the EU level), and discursive Europeanization (similar topics discussed at the same time). The findings do not identify protest as a strong driving force towards vertical or horizontal Europeanization of the public spheres in Greece and Germany. There is a weak tendency towards discussing similar topics at the same time in German and Greek media reports on protest. Consequences for European democracy and crisis politics are discussed.